Cd-Based metal–organic frameworks from solvothermal reactions involving in situ aldimine condensation and the highly sensitive detection of Fe3+ ions. Issue 7 (31st January 2017) - Zhang, Xin; Wang, Zhong-Jie; Chen, Shu-Guang; Shi, Zhen-Zhen; Chen, Jin-Xi; Zheng, He-Gen
Abstract : Four Cd(ii )-based compounds (1, 2, 3 and4 ) were synthesized involving in situ aldimine condensation, and compound2 showed an excellent sensitivity for detecting Fe 3+ ions. Abstract : Four Cd(ii )-based compounds (1–4 ) were synthesized from solvothermal reactions involving the in situ aldimine condensation of an o -diamino-functionalized precursor 3, 6-di(4 H -imidazol-4-yl)benzene-1, 2-diamine (L), Cd(NO3 )2 ·4H2 O and aldehyde. Two modes of cycloaddition ([4 + 1] cycloaddition and [4 + 2] cycloaddition) occurred during condensation, causing the in situ generation of two benzimidazole derivative ligands (L1 and L3) and a quinoxaline derivative ligand (L2). Furthermore, the chemical selectivity of the condensation was studied, where the condensation of o -diamino and the aldehyde is more stable and easy to operate. This strategy enriches the synthesis method of MOFs. Additionally, compound2 containing uncoordinated quinoxaline N atoms showed excellent luminescent sensitivity for Fe 3+ detection.